PENGUJTAN PECKTTVG ORDER THEORY (POT): Pengaruh Leverage Terhadap Pendanaan Surplus dan Defisit pada lndustri Manufaktur di Bursa Efek lndonesia - Ari Christianti (Fakultas Bisnis UKDW, 2008)
This research is empirically examines the Pecking Mer Theory eOD. This is important since the POT discuss the factors effected the tevet of debt used by tfui company srrch as: the capocity of deficit due to internal cash tlow inadequocy for exercising the hwestment and its commitment to regululy pay dividend- On doing so, this research is intended to specifically examine the effect of surphs and deficit financing on the use of debt. The samples oe dr*vn trom compoies within maruacturingsector which are listed at the Indonesiott Capital Stock Erchangeduring 2000-2005. Furthermore the data will be analyzed using the regression with dumrny vsiables. The result sltows, there is a negatively effect between long term debt with deficrt. The possible explanation is muket and economic condition effect the capital stttcryre decision. Keyword: Pecking Mer Theory eOD, debt, sarplus, deficit",